A resource of lipidomics and metabolomics data from individuals with undiagnosed diseases - Jennifer E. Kyle (Nature Portfolio, 2021)
Measurement(s) Metabolomics • Lipidomics Technology Type(s) gas chromatography-mass spectrometry • Ultra High-performance Liquid Chromatography/Tandem Mass Spectrometry Factor Type(s) age group • sex Sample Characteristic - Organism Homo sapiens Sample Characteristic - Environment blood plasma material • urine material • cerebrospinal fluid material Sample Characteristic - Location United States of America Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13656581